Discursos docentes sobre Libras e língua portuguesa na educação de surdos em escolas municipais - Couto, Benigna Maria de Assunção (Universidade do Vale do Rio dos Sinos, 2015)
This paper aims to reflect on perceptions of teachers of a primary school in the municipal state of Maranhão, and, from that, to analyze the relationship that teachers establish between the pound and the Portuguese language in deaf education. To this end, we used semi-structured interviews with five teachers in the early grades of elementary school. Reflection on such data is based on studies that turn the course of deaf education and the teaching and learning of languages, specifically Portuguese and Libras, bringing assumptions of Vygotsky on the intellectual development and learning, Tables (1997), Karnopp (2004), Fernandes (2003) about the deaf education and the Portuguese language teaching and Pounds. Among the findings of this study, it is emphasized that education of the deaf in particular, bilingual education, is coated actions focused on the search for the adequacy and standardization of deaf people. In the dialogue mediated by the data generated during the study with the research that underpinned the discussions, we see the need for more reflections on deaf education, particularly the teaching of Portuguese and Libras language, especially the scene of teaching and learning processes in which it sets the deaf education.
Keywords: Educação de surdos; Libras; Língua portuguesa; Ensino fundamental; Deaf education; Pounds; Portuguese language; Elementary school